2018
DOI: 10.2174/1874944501811010062
|View full text |Cite
|
Sign up to set email alerts
|

Non-Adherence Related Factors to Antihypertensive Medications Among Hypertensive Patients on Follow up at Nedjo General Hospital in West Ethiopia

Abstract: Background:Hypertension is an overwhelming global challenge. Increasing awareness and diagnosis of hypertension, and improving control of blood pressure with appropriate treatment are considered critical public health initiatives to reduce cardiovascular morbidity and mortality.Objective:To assess non-adherence-related factors to antihypertensive medications among hypertensive patients on follow up at Nedjo General Hospital.Methods:A cross-sectional study was conducted among hypertensive patients on follow up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 23 publications
4
29
8
1
Order By: Relevance
“…Whereas some other studies like Roy etal(15) and Berisa et al (16) found non adherence rate of 71.4% and 69.6% respectively, much higher than reported in our study. In patients with hypertension, despite the availability of effective therapy, hypertension remains poorly controlled in the developed and developing countries.…”
Section: Discussioncontrasting
confidence: 86%
“…Whereas some other studies like Roy etal(15) and Berisa et al (16) found non adherence rate of 71.4% and 69.6% respectively, much higher than reported in our study. In patients with hypertension, despite the availability of effective therapy, hypertension remains poorly controlled in the developed and developing countries.…”
Section: Discussioncontrasting
confidence: 86%
“…In other African black populations, such as those living in Ghana, Nigeria 27 and Nedjo 28 , there are lower adherence rates than those in our study, 33.3% and 31.4%, being related to the use of medicinal herbs (cultural factor), low knowledge about AH and access to drug treatment. Probably, the most frequent contact of hypertensive quilombola people in study with the urban community and the health service has reduced this cultural belief and increased the confidence and the attitudes in the drug treatment.…”
Section: Discussioncontrasting
confidence: 79%
“…The full-text papers of 31 articles were retrieved and reviewed for inclusion which resulted in a total of 18 studies eligible for the methodological quality assessment. After excluding four studies with reasons mainly a weak quality score, 14 studies were included in the final SR (qualitative synthesis) [19][20][21][22][23][24][25][26][27][28][29][30][31][32] and 12 of them were also included in MA ( Figure 1).…”
Section: Selection Of the Studiesmentioning
confidence: 99%
“…The selected studies were published between 2012 and 2019. Regarding the geographical part of the country, one study was conducted in the north, 19 four studies were in the northwest, 20,27,30,31 one study was in the northeast, 24 three studies were in the central, 26,29,32 two studies were in the western, 22,23 one study was in the southern, 28 and two studies were in the southwest. 21,25 Except for the study in Hawassa 28 which was an unmatched case-control study, all other studies were hospital-based cross-sectional quantitative in type.…”
Section: Baseline Characteristics Of Studiesmentioning
confidence: 99%